Autonomic dystonia syndrome as one of the etiofactors in the development of peptic ulcer (Journal of Universal Science Research, 2023)
Vegetovascular dystonia (VSD) is a concept that includes a whole complex of disorders that are formed due to pathology in the human body. The disease is presented in the form of various symptoms that develop against the background of a malfunction of the autonomic nervous system. In this case, the balance between the sympathetic and parasympathetic parts of the nervous system is disrupted. A person may complain of headaches, dizziness, black spots before the eyes, heart rhythm disturbances, insomnia, anxiety, and mood swings. It is believed that with this diagnosis the patient has no organic disorders, and all manifestations are functional.